Obbligato-songs : a collection of song, with accompaniment of piano and violin (or violoncello) - SPICKER, Max (ed) (G. Schirmer. Inc., 1905)
Three shadows, La Serenata, Vision, Loin de Lui, Les premiers Aveux, My heart to thee !